Upaya Meningkatkan Pemahaman Konsep Matematika Siswa Melalui Penerapan Model CORE di MA NW Putra Narmada Tahun Pelajaran 2023/2024 - Sabrun, Sabrun (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
This study was conducted as an effort to enhance students' understanding of mathematical concepts through the application of the CORE (Connecting, Organizing, Reflecting, Extending) model at MA NW Putra Narmada, West Lombok Regency. This research is a Classroom Action Research (CAR) carried out in two cycles with stages of planning, implementation, observation, and reflection. The subjects of this research are 34 students from the 10th grade at MA NW Putra Narmada. The research instruments used are observation sheets and test sheets. The data collection techniques employed are testing and observation. The data analysis techniques used are both quantitative and qualitative data analysis. The results of this study indicate an improvement in the understanding of mathematical concepts among the 10th grade students of MA NW Putra Narmada after applying the CORE learning model. Test results show an increase in students' understanding of mathematical concepts in cycle I to 57% with a sufficient category, while in cycle II, it increased to 95.00% with an excellent category. Observation results show 68% in cycle I with a good category and 96.00% in cycle II with an excellent category.